Hepatitis C virus infection in phenotypically distinct Huh7 cell lines. - Bruno Sainz; Naina Barretto; Susan L Uprichard (PLoS ONE)
In 2005, the first robust hepatitis C virus (HCV) infectious cell culture system was developed based on the HCV genotype 2a JFH-1 molecular clone and the human-derived hepatoma cell line Huh7. Although much effort has been made to dissect and expand the repertoire of JFH-1-derived clones, less attention has been given to the host cell despite the intriguing facts that thus far only Huh7 cells have been found to be highly permissive for HCV infection and furthermore only a limited number of Huh7 cell lines/stocks appear to be fully permissive. As such, we compiled a panel of Huh7 lines from disparate sources and evaluated their permissiveness for HCV infection. We found that although Huh7 lines from different laboratories do vary in morphology and cell growth, the majority (8 out of 9) were highly permissive for infection, as demonstrated by robust HCV RNA and de novo infectious virion production following infection. While HCV RNA levels achieved in the 8 permissive cell lines were relatively equivalent, three Huh7 lines demonstrated higher infectious virion production suggesting these cell lines more efficiently support post-replication event(s) in the viral life cycle. Consistent with previous studies, the single Huh7 line found to be relatively resistant to infection demonstrated a block in HCV entry. These studies not only suggest that the majority of Huh7 cell lines in different laboratories are in fact highly permissive for HCV infection, but also identify phenotypically distinct Huh7 lines, which may facilitate studies investigating the cellular determinants of HCV infection.